2016
DOI: 10.1177/0091415016668353
|View full text |Cite
|
Sign up to set email alerts
|

Friendship Repertoires and Care Arrangement

Abstract: Friends are important companions and serve as sources for diverse dimensions of social support, including elderly care. Rather than researching populations that have already established care arrangements including friends, the author seeks to understand relationship systems with a focus on the inner logic friendship to consequently describe and understand involved care arrangements, be it with family members or friends. To illustrate the diversity of friendship repertoires, qualitative interviews with older ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 80 publications
0
0
1
Order By: Relevance
“…The concept of reciprocity in the care of older persons by family members emerged as a powerful norm in the results of this study of community leaders' perspectives in Zambia. It differs from the evidence presented in studies undertaken in Britain and Germany (Finch and Mason, 1991;Hahmann, 2017), which showed that in those countries, reciprocity was not the main driver in mutual family support. From the views of the community leaders who participated in this study, it seems that norms of reciprocity are real in Zambia; they were prevalent in their rhetoric and understanding.…”
Section: Discussioncontrasting
confidence: 98%
“…The concept of reciprocity in the care of older persons by family members emerged as a powerful norm in the results of this study of community leaders' perspectives in Zambia. It differs from the evidence presented in studies undertaken in Britain and Germany (Finch and Mason, 1991;Hahmann, 2017), which showed that in those countries, reciprocity was not the main driver in mutual family support. From the views of the community leaders who participated in this study, it seems that norms of reciprocity are real in Zambia; they were prevalent in their rhetoric and understanding.…”
Section: Discussioncontrasting
confidence: 98%